A certain tickling humour : English travellers, 1560-1660 - Ghazvinian, J (2003)
The story of early modern English travellers has generally been treated by scholars as a subplot to larger narratives - whether political history, art history, or, more recently, textual criticism and constructions of the 'other'. It has never been discussed as a distinct development within the cultural history of England, with a narrative of its own. Furthermore, historians have traditionally explained away, dismissed as irrelevant, or simply ignored the fact that a growing number of travellers claimed to be motivated by their 'mere curiosity to see', rather than recognising it as a critical aspect of the new phenomenon. This thesis attempts to be a corrective to both these tendencies. It begins with the relationship between the traveller and the State, answering questions about the government's attitude to travel, the process of getting a licence to go abroad, fears about Catholic conversion, and how these things changed over time. It goes on to answer basic questions about who was travelling and what the tour abroad was actually like. The results of an exhaustive study of nearly 2,000 passport records are presented, in an effort to demonstrate the growing popularity of foreign travel in these years. Part Two focuses on the vigorous debate over the value of travel for the young, and the genre of travel advice literature that arose over time. The hostility evoked by the idea of 'curiosity', as well as concerns over travellers being too young, are discussed. The final part of the thesis challenges the assumption that this period merely witnessed the 'rise of the Grand Tour'. Travel to Spa for the recovery of health and the growth of domestic resorts such as Bath and Buxton are looked at, while a final chapter examines those travellers who extended their tours beyond Europe, and ventured into the Levant and beyond.